2009
DOI: 10.3139/113.110037
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Solution Properties, Biodegradability, and Antimicrobial Activity of some Alkylpolyglycosides Surfactants

Abstract: In the present investigation, a series of alkyl polyglycosides with alkyl chain length of C 8, 9, 10, 12 and 14 were synthesized using transacetalization method. Purity of the products was investigated using high performance liquid chromatography. Surface parameters particularly Effectiveness πcmc, Efficiency Pc20, maximum surface excess Γmax, minimum surface area Amin and HLB values are investigated, in addition to thermodynamic parameters (ΔGads and ΔGmic). Resistance to hydrolysis for the prepared compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Figure 7 shows the proposed biodegradation pathways of APG 650. These pathways are a result of considering the APG biodegradation pathways found in literature (Eichhorn and Knepper, 1999;El-Sukkary et al, 2009;Qin et al, 2006;Zgola-Grzeskowiak et al, 2008;Zhang et al, 2003) and the results reported by these authors. Quiroga and Sales (1991) and first-order model for stages A and B, respectively.…”
Section: Resultsmentioning
confidence: 69%
“…Figure 7 shows the proposed biodegradation pathways of APG 650. These pathways are a result of considering the APG biodegradation pathways found in literature (Eichhorn and Knepper, 1999;El-Sukkary et al, 2009;Qin et al, 2006;Zgola-Grzeskowiak et al, 2008;Zhang et al, 2003) and the results reported by these authors. Quiroga and Sales (1991) and first-order model for stages A and B, respectively.…”
Section: Resultsmentioning
confidence: 69%
“…That leads to the penetration of several components to the cellular cytoplasm including counter ions and combination occur with the (nucleic acids) DNA and RNA. Hence, the biological reactions disturbed which cause death for these microorganisms [15][16].…”
Section: Measurementsmentioning
confidence: 99%
“…Biodegradability test in river water of the Gemini cationic surfactant was determined by the surface tension method using a Dü -Nouy tensiometer (Krü ss type K6) [26][27][28]. In this method, each surfactant was dissolved in river water by a concentration of 100 ppm and incubated at 38 8C.…”
Section: Biodegradabilitymentioning
confidence: 99%